GlobalAMFungi: a global database of arbuscular mycorrhizal fungal occurrences from high-throughput sequencing metabarcoding studies - Větrovský, Tomáš; Kolaříková, Zuzana; Lepinay, Clémentine; Awokunle Hollá, Sandra; Davison, John; Fleyberková, Anna; Gromyko, Anastasiia; Jelínková, Barbora; Kolařík, Miroslav; Krüger, Manuela; Lejsková, Renata; Michalčíková, Lenka; et al. (The New phytologist, 2023)
Arbuscular mycorrhizal (AM) fungi are crucial mutualistic symbionts of the majority of plant species, with essential roles in plant nutrient uptake and stress mitigation. The importance of AM fungi in ecosystems contrasts with our limited understanding of the patterns of AM fungal biogeography and the environmental factors that drive those patterns. This article presents a release of a newly developed global AM fungal dataset (GlobalAMFungi database, https://globalamfungi.com) that aims to reduce this knowledge gap. It contains almost 50 million observations of Glomeromycotinian AM fungal amplicon DNA sequences across almost 8500 samples with geographical locations and additional metadata obtained from 100 original studies. The GlobalAMFungi database is built on sequencing data originating from AM fungal taxon barcoding regions in: i) the small subunit rRNA (SSU) gene; ii) the internal transcribed spacer 2 (ITS2) region; and iii) the large subunit rRNA (LSU) gene. The GlobalAMFungi database is an open source and open access initiative that compiles the most comprehensive atlas of AM fungal distribution. It is designed as a permanent effort that will be continuously updated by its creators and through the collaboration of the scientific community. This study also documented applicability of the dataset to better understand ecology of AM fungal taxa.
Keywords: symbióza; Mycorrhizae; fungal biogeography; rostliny; Plants; glomeromycota; ekosystém; půdní mikrobiologie; glomeromycotina; high-throughput sequencing; Symbiosis; fungal diversity; Soil Microbiology; mykorhiza; arbuscular mycorrhizal fungi; Ecosystem; vysoce účinné nukleotidové sekvenování; High-Throughput Nucleotide Sequencing